Preliminary references: Analyzing the determinants that made the ECJ the powerful court it is - Lars Hornuf; Stefan Voigt (Center for Economic Studies and ifo Institute (CESifo), 2012)
The European Court of Justice (ECJ) is a very powerful court compared to other international courts and even national courts of last resort. Observers almost unanimously agree that it is the preliminary references procedure that made the ECJ the powerful court it is today. In this paper, we analyze the determinants that lead national courts to use the procedure. We add to previous studies by constructing a comprehensive panel dataset (1982-2008), including more potentially relevant explanatory variables and by testing for the robustness of previous results. In addition to confirming the relevance of variables previously found significant, we identify a number of additional determinants, including the relevance of agriculture to a country, corporate tax rate, familiarity with EU law, and tenure of democracy.
Keywords: H77; K33; 330; European Court of Justice; economic analysis of court behavior; preliminary reference procedure; Gerichtsbarkeit; Verfahrensrecht; Rechtsökonomik; Schätzung; EU-Staaten